Concession period determination for PPP retirement village - Liu, Shijing; Jin, Hongyu; Xie, Benzheng; Liu, Chunlu; Mills, Anthony (International Journal of Strategic Property Management, 2018)
Demand for the construction of retirement villages is increasing with the worldwide growth in ageing populations. However, the development of retirement villages can be impeded by many factors, such as limited available land and high investment costs. Public–private partnership (PPP) as an alternative financing mechanism has been widely applied in the construction of public infrastructure projects and may provide new funding sources for building retirement villages. By applying PPP to the construction of retirement villages, the independent living requirements of seniors can be met and the financial difficulty of the construction of retirement villages can be resolved. Similar to other PPP projects, when retirement villages are constructed under a PPP process, the concession period is a key decision variable in relation to the success of the project. The concession period is stated in the project contract between the government and private investors, and stipulates the date when the project ownership and operation are transferred from the private investor back to the government. The government should take detailed information into consideration at the initial project stage when determining the concession period. This paper proposes PPP as a new procurement method to be applied to the construction of rental retirement villages and develops a concession period determination process for PPP retirement village projects with consideration of real options, focusing on the option to defer. An empirical example with alternative scales, which is developed from an existing retirement village in Geelong, Australia, is used to numerically verify the process and the impacts of key variables on the concession period. The determination process provides an alternative tool for governments to design the concession period before the tendering stage and will benefit the development of industries associated with services for the ageing population. This process can also be applied to the construction of other financially non-viable PPP projects such as social housing.